Increase in adiposity from childhood to adulthood predicts a metabolically obese phenotype in normal-weight adults - A. Viitasalo; N. Pitkänen; K. Pahkala; T. Lehtimäki; J. S. A. Viikari; O. Raitakari; T. O. Kilpeläinen (Springer Nature, 2022)
Normal weight is associated with a favorable cardiometabolic risk profile and low risk of type 2 diabetes and cardiovascular disease. However, some normal-weight individuals—the “metabolically obese normal weight” (MONW)—show a cardiometabolic risk profile similar to the obese. Previous studies have shown that older age, central body fat distribution, and unfavorable lifestyle increase the risk of MONW. However, the role of early-life factors in MONW remains unknown. We examined the associations of early-life factors with adult MONW in 1178 individuals from the Cardiovascular Risk in Young Finns study who were followed up from childhood to adulthood. The strongest early predictor for adult MONW was an increase in BMI from childhood to adulthood (p = 3.1 × 10−11); each 1 SD increase in BMI z-score from childhood to adulthood led to a 2.56-fold increase in the risk of adult MONW (CI 95% = 1.94–3.38). Other significant predictors of adult MONW were male sex (OR = 2.38, 95% = 1.63–3.47, p = 7.0 × 10−6), higher childhood LDL cholesterol (OR = 1.41 per 1 SD increase in LDL cholesterol, CI 95% = 1.14–1.73, p = 0.001), and lower HDL cholesterol (OR = 1.51 per 1 SD decrease in HDL cholesterol, CI 95% = 1.23–1.85, p = 5.4 × 10−5). Our results suggest that an increase in adiposity from childhood to adulthood is detrimental to cardiometabolic health, even among individuals remaining normal weight.